Sistem Pendukung Keputusan Pemilihan Sneakers Hak Tinggi Untuk Konser Menggunakan Metode MOORA - Shella Cintiya; Wahyu Tisno Atmojo (Peneliti.net, 2023)
In a concert, there are usually two types of audience places, standing and seating. In general, the audience will choose to stand because they are closer to the artist and have more freedom to move. However, the height problem makes it difficult for people with below average height to see the stage. One of the solutions is to use footwear with high heels. However, during standing there is the possibility of the audience accidentally stepping on other audience members' feet and the long duration of the concert requires the audience to choose comfortable footwear so sneakers are the most suitable type. Not only that, another problem arises when they want to choose which product is the best, especially with the many brands with different variations making buyers confused about which high heel sneaker brand is suitable. Therefore, a system was created that could help select high-heeled sneakers brands, namely a decision support system for selecting high-heeled sneakers utilizing the MOORA approach. From the outcomes of calculations with the MOORA method, the first rank was Converse Run Star Motion. Based on these output, it can help people who are going to the concert to choose the appropriate high heels sneakers.